Difficulties of the interpretation and hermeneutical understanding of the text: writing, appropriation and meaning. A reading proposal from Sartre and Ricoeur - Rojas Valdés, Mitchel Angelo (2022)
This writing seeks to expose, in a limited way, a problem inherent to the hermeneutical interpretation of texts: how to ensure adequate understanding of the text, how to gain access to the meaning of the text; in other words, through what procedures a good interpretation of the text in front of there can be ensured. For this reason, the difficulties that arise in the interpretive task will be highlighted: the situation of historical-temporal distancing and its duplicity character, the problem of the author’s intention or the autonomy of the text, the problem of the unity of meaning of the text or the plurality of this that makes erosion and bursts like flow in the writing, etc. These difficulties lead to a radical approach to the question for the plausibility of a hermeneutical interpretation of the text. To address this task and probe the aforementioned difficulties, the proposals of authors such as Gadamer, Sartre, Ricoeur, Barthes and Derrida will be briefly weighed, supporting that a possible solution would be in some “reading” proposals that unfold from the Sartrean and Ricoeurian position.